Optimization Of Islamic Counseling And Understanding Of Well Being in Reducing Anxiety and Stress In Face-To-Face Learning After The Covid-19 Pandemic - Anniez Rachmawati Musslifah (Chakra Brahmanda Lentera Institute, 2022)
Background: This paper aims to find out the influence of Islamic counseling and understanding of the concept of well-being on reducing anxiety and stress in student guardians since the start of face-to-face learning after the decline of the Covid-19 emergency.. Methods: This research is quantitative research with a quasi-experimental approach. A total of 32 respondents were taken using convenience sampling Results: Understanding wellbeing showed a decrease in anxiety rate of 14.5%, while stress showed a 12.7% decrease. Islamic counseling showed a decrease in anxiety rate of 17.8%, while stress showed a 16.4% decrease. Student guardians given both treatments, Islamic counseling, and well-being comprehension showed a 12.7% reduction in anxiety and a 7.08% reduction in stress. The results showed that Islamic counseling is significantly more beneficial in lowering anxiety and stress than providing an understanding of wellbeing. Conclusion: The provision of Islamic counseling in this study showed more success rates in reducing anxiety and stress in student guardians compared to providing an understanding of the concept of wellbeing. The decrease in anxiety and stress was higher indicated by subjects who received both treatment, Islamic counseling, and the provision of understanding of the concept of wellbeing